2014 CESA Awards II: Honouring excellence. Issue 1 (January 2015) - Unknown
Abstract : IN PART I of this feature ( REFocus November-December), we looked at three of the eight installations recognized by judges on the 2014 CESA Awards panel. This second and final installment focuses on the remaining five winners.